2009
DOI: 10.1021/bi900909g
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Polar Residues Stabilize Transmembrane Domains and Promote Oligomerization in Human Nucleoside Triphosphate Diphosphohydrolase 3

Abstract: Polar residues play essential roles in the functions of transmembrane helices by mediating and stabilizing their helical interactions. To investigate the structural/functional roles of the conserved polar residues in the N-and C-terminal transmembrane helices of human NTPDase3 (N-terminal: S33, S39, T41, and Q44; C-terminal: T490, T495, and C501), each was singly mutated to alanine. The mutant proteins were analyzed for enzymatic activities, glycosylation status, expression level, and Triton X-100 detergent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Dimer formation cannot occur when Q44 is mutated resulting in loss of activity to a similar level as seen with the wild-type enzyme in the presence of Triton X-100. In the same study, the authors obtained the surprising result that NTPDase3 dimer persisted in the presence of Tween-20 and the activity was stimulated 2.5-fold [89]. This effect is unique to NTPDase3 since Tween-20 inhibited both NTPDases 1 and 2.…”
Section: )mentioning
confidence: 86%
See 1 more Smart Citation
“…Dimer formation cannot occur when Q44 is mutated resulting in loss of activity to a similar level as seen with the wild-type enzyme in the presence of Triton X-100. In the same study, the authors obtained the surprising result that NTPDase3 dimer persisted in the presence of Tween-20 and the activity was stimulated 2.5-fold [89]. This effect is unique to NTPDase3 since Tween-20 inhibited both NTPDases 1 and 2.…”
Section: )mentioning
confidence: 86%
“…While evidence for a stable tetrameric NTPDase is generally lacking, Gaddie and Kirley [89] recently provided strong evidence for the existence of a stable dimer for the full-length human NTPDase3. NTPDase3 of many species has a conserved glutamine (Q44 in human NTPDase3) that is located in TMD1 and near the extracellular surface.…”
Section: )mentioning
confidence: 99%
“…Human NTPDase3 was found to preferentially form dimers [138]. Hydrogen bonding involving a conserved glutamine located in TMD1 near the extracellular surface was implicated in dimer formation [141]. The variable oligomeric structure of NTPDases from monomeric to oligomeric forms is in stark contrast to P2X receptors that share similar membrane topology [142].…”
Section: Oligomeric Structurementioning
confidence: 99%
“…Members of the ASKHA structural superfamily are renowned for especially large conformational transitions coupled to function (e.g., Factin versus G-actin). A multitude of experiments have shown that a strong linkage exists between the active site and transmembrane helix interactions [71, 73,125,132,133,141,197]. Oxidative cross-linking experiments carried out with cysteine mutants of membrane-bound variants of NTPDase1 indicate a rather dynamic coupling of coordinated movements of the transmembrane helices to spatial rearrangements of the active site [125,132,133].…”
Section: Active Site and Catalytic Mechanismmentioning
confidence: 99%
See 1 more Smart Citation